Training on Digital Marketing, Operational Management and Visual Communication Design in Serving International Guests at “Glagah Linggah Lestari” Forest Farmer Group, Kintamani, Bali, Indonesia - ELFAROSA, Ketut Vini; PUTRA, Kadek Dwi Cahaya; SARASWATI, Ni Putu Ritra Trees Ari Kartika Hadi; HAPSARI, Yulia Tria; PARWITA, Wayan Gede Suka (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Glagah Linggah Forest Farmer Group is a farmer group that was given the trust by the Manikliyu traditional village to manage Glagah Linggah Pine Tourism. So far, they have received assistance from various companies, one of which is PT Tirta Investama, one of the industrial partners of the International Business Management study program. In the coaching conducted by PT Tirta Investama, there were several problems faced and they needed help from the campus in training digital marketing, operations, and communication design in serving international guests. Because so far when there are international guests, officers are less able to communicate. In addition, in terms of operational management, to welcome international guests and explain the facilities are also still limited, so it requires service excellence training. Facilities for bilingual and digital information are also limited. Marketing advertisements, mostly in Indonesia, have not penetrated marketing for international guests. So that this Community Service will later collaborate with PT Tirta Investama, where the campus will conduct training on how to welcome guests through service excellence and create some marketing content; communication design is expected to help smooth the operation of this Glagah Linggah pine forest tour. With this Community Service, it is hoped that this forest tour can develop its marketing more broadly to the international market supported by the service capabilities of officers and visual communication that is more supportive for international guests.